Evaluation of potential serum biomarkers of hepatic fibrosis and necroinflammatory activity in dogs with liver disease. (27th February 2018) - Raghu, Chantel; Ekena, Joanne; Cullen, John M.; Webb, Craig B.; Trepanier, Lauren A.
Abstract : Background: Serum interleukin 6 (IL‐6), chemokine ligand 2 (CCL2), C‐reactive protein (CRP), and the ratio of aspartate transaminase to alanine transaminase (AST:ALT) have been correlated with fibrosis and necroinflammatory activity in humans with various hepatopathies. Hypothesis/Objectives: To determine whether increases in serum IL‐6, CCL2, CRP, or AST:ALT were associated with moderate to severe fibrosis or necroinflammatory activity in dogs with various hepatopathies. Animals: Forty‐four client‐owned dogs with clinical evidence of liver disease and 10 healthy purpose‐bred dogs, all undergoing liver biopsies by laparoscopy or laparotomy. Methods: Measurement of serum IL‐6, CCL2, CRP, AST, and ALT before scheduled liver biopsy and evaluation of liver histopathology using the METAVIR scoring system used in human medicine, blinded to clinical presentation. Results: Median serum IL‐6 was approximately twice as high in dogs with high fibrosis scores (15.5 pg/mL; range, 1.4 to 235 pg/mL) compared to dogs with low fibrosis scores (7.6 pg/mL; range, 1.4 to 148.1 pg/mL), with marginal significance ( P  = .05). Median serum CCL2 was significantly higher in dogs with active necroinflammation (444 pg/mL; range, 144 to 896 pg/mL) compared to dogs without detectable necroinflammation (326 pg/mL; range, 59 to 1692 pg/mL; P  = .008), but with considerable overlap between groups. Neither serum CRP nor AST:ALT ratios were significantly different based on fibrosis or necroinflammatory scores. Conclusions and Clinical Importance: Because of substantial variability among dogs, single measurements of IL‐6 and CCL2 have limited diagnostic utility for identifying fibrosis or necroinflammation, respectively, in dogs with various chronic liver diseases. The value of these biomarkers should be explored further in monitoring response to treatment in individual dogs with chronic hepatopathies.